(untitled) (Journal of the College of Basic Education, 2022)
The research aimed to know the level of decision-making among students of the College of Law, and to achieve this, the researcher adopted a scale (Ibrahim 2004) to measure the ability to make decisions after extracting honesty and consistency for it and ensuring its suitability to the research community by presenting it to a number of experts and specialists, and a sample of (100) students was chosen. A student from the second and fourth stage students at the College of Law - University of Al-Qadisiyah for the academic year 2020-2021, It was selected randomly and it became clear that the sample members are characterized by a high level of decision-making. Also, there is no difference between females and males in the level of decision-making. While there is a difference between the students of the second and fourth stage in the level of decision-making in favor of the students of the fourth stage, the research came out with a number of recommendations and proposals, including the need to enable students to develop their decision-making ability and invest it and develop students’ skill in the field of measuring and applying decision-making ability.